A PROFILE OF ACADEMIC BURNOUT AMONG 11TH-GRADE VOCATIONAL HIGH SCHOOL STUDENTS AT THE KADIPATEN STATE VOCATIONAL HIGH SCHOOL IN TASIKMALAYA - Indriyani Wardhatul; Cucu Arumsari; Feida Noorlaila Isti'adah (Jurnal Kajian Pendidikan dan Psikologi, 2026)
Academic burnout is a psychological issue that can arise when students face constant academic demands. This condition is particularly relevant for students at Vocational High Schools (SMK) because they must juggle theoretical coursework, vocational training, assignments, and preparation for entering the workforce. This study aims to provide an overview of academic burnout among 11th-grade students at SMKN Kadipaten Tasikmalaya based on three aspects: exhaustion, cynicism, and reduced professional efficacy. The study employs a quantitative approach using a descriptive method. The study population consisted of 519 11th-grade students from seven vocational programs. The sample comprised 218 students selected using proportionate stratified random sampling. Data were collected using an academic burnout scale adapted from the Maslach Burnout Inventory–Student Survey (MBI-SS) with 23 valid items and analyzed using descriptive statistics with IBM SPSS Statistics 25. The results showed that academic burnout was generally in the moderate category, with 185 students (84.9%) in the moderate category and 33 students (15.1%) in the high category. No students were in the low category. By dimension, exhaustion was in the moderate category at 91.3%, cynicism at 91.7%, and reduced professional efficacy at 89.4%. These findings indicate that academic burnout has not yet reached an alarming level but requires preventive attention through guidance and counseling services to help students manage academic stress, maintain their motivation to learn, and boost their confidence in their academic abilities.